Updating Visibility Chart Bandar Udara Internasional Sultan Hasanuddin Makassar - Aga, Girvinia Apriyanti; Kona, Musri (SKY EAST: Education of Aviation Science and Technology, 2023)
This research aims to update the Aerodrome Visibility Chart at Sultan Hasanuddin International Airport in Makassar. The research method used is qualitative, conducting observations on the research object, namely the Aerodrome Visibility Chart. The results of the study indicate the presence of 5 points that can serve as references in updating the Aerodrome Visibility Chart at Sultan Hasanuddin International Airport. These points include the Radio Antenna, Holten Dalton Building (as an update from Grand Quality Hotel), Taman Sari Development Project, New Terminal Building, and Grand Mall Maros. The conclusion of this research emphasizes the need to update the Aerodrome Visibility Chart at Sultan Hasanuddin International Airport, taking into account the identified points, in order to provide more accurate and relevant information regarding visibility conditions around the airport.